2018
DOI: 10.1111/ggi.13498
|View full text |Cite
|
Sign up to set email alerts
|

Association between dynapenia and decline in higher‐level functional capacity in older men with diabetes

Abstract: A statistically significant association was found between dynapenia and decline of higher-level functional capacity in older men with diabetes. Geriatr Gerontol Int 2018; 18: 1393-1397.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…In previous studies in diabetic patients aged ≥ 65 years, the frequency of sarcopenia has been reported to range from 5.8% to 15.3% [ 24 , 25 ]. A study investigating frequencies of sarcopenia in different age groups [ 24 ] reported a frequency of 13.9% in those approximately 75 years of age, which is the mean age of participants in our study; rates in this study and ours are similar.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies in diabetic patients aged ≥ 65 years, the frequency of sarcopenia has been reported to range from 5.8% to 15.3% [ 24 , 25 ]. A study investigating frequencies of sarcopenia in different age groups [ 24 ] reported a frequency of 13.9% in those approximately 75 years of age, which is the mean age of participants in our study; rates in this study and ours are similar.…”
Section: Discussionmentioning
confidence: 99%
“…Higher-level functional capacity comprises the top three levels, as defined by Lawton [ 1 ]: social role (SR), intellectual activity (IA), and instrumental activities of daily living (IADL). Higher-level functional capacity is associated with adverse health outcomes such as death [ 2 , 3 ], stroke [ 4 ], dynapenia [ 5 ], and subjective memory complaints [ 6 ]. Maintaining a higher functional capacity to live independently in old age is extremely important.…”
Section: Introductionmentioning
confidence: 99%
“…Показатель выявляемости с использованием указанных методик (12,8-38,2 %) зависит от пола, возраста, имеющихся заболеваний, их стадии, эффективности лечения: у мужчин -до 21,8 %, у женщин -до 30,4 %[64,65]. Наличие пресаркопении констатируется при индексе мышечной массы скелета до 7,26 кг/м 2 у мужчин, до 5,5 кг/м 2 -у женщин[66,67].…”
unclassified